Genomic insights into southern white rhinoceros (Ceratotherium simum simum) reproduction: Revealing granulosa cell gene expression - Elena Ruggeri; Kristin Klohonatz; Marc-André Sirard; Barbara Durrant; Stephen Coleman (Theriogenology Wild, 2023)
In vivo-collected granulosa cells (GC) from the southern white rhinoceros (SWR) provide a non-invasive assessment of the developmental status of oocytes prior to in vitro culture, which could aid in the development of assisted reproductive technologies (ART). Our study aimed to investigate gene expression in SWR granulosa cells, collected in vivo and gain preliminary insight into the transcriptional activity occurring within the cells during various stages of oocyte development. It was hypothesized there would be similarities between the SWR GC transcriptome and cattle and humans, two species for which well-annotated genomes are available and ART are commonly used. GC were collected from SWR following ovum pickup (OPU) and pooled from all aspirated follicles. Total RNA was isolated, libraries prepared, and sequencing performed using an Illumina NextSeq 500. Reads were aligned and annotated to CerSimCot1.0. Databases for cattle and human were acquired for comparison. This study identified 37,407 transcripts present in GC of SWR. It was determined that cattle and human transcriptomes are valuable resources with a homology of 45 % with the SWR. In conclusion, these data provide preliminary, novel insights into the transcriptional activity of GC in the SWR that can be used to enhance ART in this species.